The intrinsic variability of the Indonesian Throughflow - Furue, Ryo; Nonaka, Masami; Sasaki, Hideharu (Frontiers in Marine Science, 2023)
The Indonesian Throughflow (ITF) carries an annual average of about 15 Sv of water from the Pacific through the Indonesian Seas Into the Indian Ocean, and its year-to-year variation ranges from 1 to 4 Sv. A 10-member ensemble of 41-year integrations of a semi-global eddy-resolving oceanic general circulation model is examined to explore the intrinsic (chaotic) variability of the ITF transport and associated flow. It is found that the annual-mean ITF transport is different by about 1 Sv between the ensemble members at several years. The characteristic vertical and horizontal structures of the ensemble anomaly (deviation from the ensemble average) are described. These structures and the basin-scale spread of the anomaly suggest that the intrinsic variability of the ITF is a genuine increase or decrease of the classical ITF rather than variability due to local eddies or nonlinear currents within the Indonesian Seas. The lagged correlation of the intrinsic component of the ITF transport with sea-surface height and barotropic streamfunction suggests that the intrinsic variability may come from zonal jets in the western subtropical North Pacific.